(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The optimum turning conditions for 42CrMo4 hardened steel, defined and recommended in the literature, are valid only for certain cutting tools and machine tools. In this paper, an attempt has been made to optimize the cutting parameters for CNC turning with robotic power supply of the machine tool by using a new type of CVD coated replaceable carbide insert as cutting tool. To determine the optimal cutting conditions such as cutting speed, feed and depth of cut, a multi-objective optimization, based on a genetic algorithm, was conducted. The generalized arithmetic mean utility function with weighting coefficients has been chosen as the optimization parameter, which is a complex index characterizing the cutting tool lifetime and production rate in turning. The optimization problem has been solved in the following sequence: 1) a model of the generalized utility function was created, reflecting the complex influence of the turning process parameters; 2) the optimal cutting conditions were determined, under which the generalized utility function has a maximum; 3) Pareto optimal solutions were found, which guarantee the best combination between tool lifetime and production rate in turning.